Comparison of outcomes of incremental vs. standard peritoneal dialysis: a systematic review and meta-analysis - Shuang Xu; Weifei Wu; Jing Cheng (BMC Nephrology, 2024)
Abstract Background Incremental peritoneal dialysis (IPD) refers to the use of less than standard full-dose peritoneal dialysis (SPD) in end-stage renal disease patients. While the use of IPD is being reported in the literature, its safety and efficacy vs. SPD is unclear. We hereby performed a systematic review of studies comparing mortality, peritonitis, technique survival, anuria-free survival and residual renal function (RRF) between IPD and SPD. Methods All comparative studies published on PubMed, Embase, CENTRAL, Scopus, and Web of Science databases from inception to 5th September 2023 and reporting on given outcomes were eligible. Results Ten studies were included. Definitions of IPD were heterogenous and hence mostly a qualitative synthesis was undertaken. Majority of studies found no difference in patient survival between IPD and SPD. Meta-analysis of crude mortality data also presented no significant difference. Peritonitis and technique survival were also not significantly different between IPD and SPD in the majority of studies. Data on RRF was conflicting. Some studies showed that IPD was associated with the preservation of RRF while others found no such difference. Conclusion IPD may be a safe alternative to SPD in incident dialysis patients. There seems to be no difference in patient survival, peritonitis, and technique survival between the two modalities. However, the impact of IPD on RRF is still questionable. Evidence is heterogeneous and conflicting to derive firm conclusions.